IMPACT OF ECONOMIC IN INDONESIA FROM COVID-19: Bachelor of Science in Business Administration - Garry Alfonsius (Universal Journal, 2020)
During coronavirus in Indonesia many people lost the job. People used to work well but today they have to contend with the current situation. Indonesia is one of the countries affected by the corona virus with a population of no. 4 in the world with a population of 270 million people this makes it very vulnerable to the spread of this virus corona, data published in March 2020 announced there were 2 positive patients affected by the corona virus, 2 months later there was an increase of thousands of percent of people infected with this virus, causing panic and fear throughout the community and bring tremendous impact from starting panic buying people buy staples in large quantities so that goods become scarce resulting in uncontrolled prices, hoarding and smuggling of personal protective equipment such as masks and personal protective clothing which makes the situation of the community increasingly haunted Fright. The Government of Indonesia has allocated a budget of Rp. 405.1 Trillion to tackle the spread of this epidemic and the impacts arising from this virus, such as decreased public purchasing power, unemployment due to massive layoffs and the sharp rise in poverty rates caused by this virus.